Hikaye-i Zen Dost or Hikaye-i Mekr-i Zenan-i Acüz (Critical edition, textual analysis, glossary) - Akman, Fatma. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
Hikaye-i zen Dost or Hikaye-i Mekr-i Zenan-i Acüz is a short story which was written in the eighteenth century with the genre of inşa (inşa prose). The language of the story is hard to understand because of its style which is inşa·. Despite the difficulty of the language, the theme of the story is quite fun and understandable. The story is about a lecherous man's attempt to seize a woman who can defined as an object of desire. In general, the story which is considered quite obscene in some parts advances event-driven and it is written with the moral purpose. The main goal of the story is to give a message, "men must be smart" and it reinforces the message with some specific events in the story. Thefore, male and female characters in the story have been fictionalized within the social perceptions of sex and gender and their roles have been determined in this direction. As well as events around the characters, careful use of lamguage and quite conscious word choices make the story more colorful, layered and literary. In this study, Hikaye-i zen Dost or Hikaye-i Mekr-i Zenan-i Acüz's text is to be transliterated with critical edition and examined according to its form and context. In the first chapter, author of the story and manuscripts used in prepering the text has been described. In the second chapter, a summary of the story, its thematic and structural features and its analysis in the context of the sex and gender have been given. In the third chapter the text is transliterated with critical edition. In the fourth, Arabic and Persian sections and their Turkish translations have been given. In the fifth, the dictionary of the work have been added. In the final the three manuscripts of the story have been addedand after that bibliography of work have been given.
Keywords: Short stories, Turkish -- 18th century.